Second Language Acquisition and Grammar Instruction - Bhowmik, Subrata Kumar (EAST WEST JOURNAL OF HUMANITIES, 2010)
Grammar instruction is a contentious issue in the field of second language acquisition. There are arguments about whether or not grammar instruction helps L2 learning. The paper reviews literature on second language acquisition research and theories to present different perspectives on the teaching of grammar. Research suggests that although grammar instruction impacts L2 learning positively it is imperative to take a cautious approach while incorporating grammar teaching in the curriculum.